Sobre a estabilidade estrutural e regularizações de campos de vetores descontínuos - Jorge, Ronan Felipe [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The concept of structural stability was introduced into the studies of continuous dynamical systems by Andronov and Pontryagin (1937). In 1988, after investigating oscillators with Coulomb friction and differential equations with discontinuous right-hand sides, Filippov developed a nomenclature to the study of discontinuous dynamical systems. Since then, researches have been trying to analyze the structural stability of discontinuous dynamical systems by different methods. One of these methods is to transform, without changing the structure of vector fields, these discontinuous systems in continuous systems where the study of structural stability is already known. This transformation, also known as regularization, can be developed in various ways. This work aims at presenting a regularization method using a transition function of vector fields Z in the plane with a discontinuous set S basing in regularization method presented by Sotomayor and Teixeira (1996) in their article, and, also to do a short study about structural stability in regularized vector fields using this method.

O conceito de estabilidade estrutural foi introduzido aos estudos de sistemas dinâmicos contínuos por Andronov e Pontryagin (1937). Em 1988, após investigar osciladores com atrito de Coulomb e apresentar equações diferenciais com lado direito descontínuo, Filippov desenvolveu em sua obra uma nomenclatura para o estudo de sistemas dinâmicos descontínuos. Desde então, estudiosos da área vêm tentando analisar a estabilidade estrutural de sistemas dinâmicos descontínuos por diferentes métodos. Um dos métodos é transformar, sem alterar a estrutura dos campos de vetores, estes sistemas descontínuos em sistemas contínuos onde o estudo da estabilidade estrutural já é conhecido. Esta transformação, também conhecida como regularização, pode ser desenvolvida de diversas formas. Este trabalho tem por objetivo a apresentação de um método de regularização através do uso de uma função de transição de campos de vetores Z do plano com um conjunto de descontinuidade S baseando-se no método de regularização apresentado por Sotomayor e Teixeira (1996) em seu artigo, e realizar um breve estudo sobre estabilidade estrutural em campos de vetores regularizados utilizando tal método.
About the structural stability and regularizations of discontinuous vector fields
Keywords: Discontinuous systems; Regularization; Structural stability; Sistemas descontínuos; Regularização; Estabilidade Estrutural